MODEL MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) DENGAN MENGINTEGRASIKAN MEDIA TIK UNTUK MENINGKATKAN KREATIVITAS SISWA MEMBUAT KARYA DUA DIMENSI DARI BENTUK BANGUN DATAR DI TK AL WAFA: Model PjBL Meningkatkan Kreatifitas Siswa - ni made mardiana astikawati (LPPM Universitas Widya Dharma, 2023)
PjBL integrated with information and communication technology (ICT) enhances students’ creativity at Al Wafa Kindergarten. The research is motivated by the lack of teachers’ ability to design innovative learning models, impacting students’ creativity. The study aims to improve students’ creativity in creating two-dimensional work from geometric shapes. The research is classified as classroom Action Research (CAR). The subjects are 8 students from Class A at Al Wafa Kindergarten in Nganjuk, comprising 7 males and 1 female. The car design follows the Kemmis and Taggart model, including planning, action, observation and reflection. Data collection techniques involve observation and documentation. Data analysis employs qualitative descriptions with statistical calculations. The research results show improvement in four indicators from the pre-cycle, cycle I and cycle II. The indicator of skill in arranging shape increased from 54.2% in the pre-cycle, 79.2% in cycle I and 87.5% in cycle II. The indicator of using a variety of flat geometric shapes increased from 54.2% in the pre-cycle, 75.0% in cycle I and 87.5% in cycle II. The indicator of neatness in creating shape increased from 62.5% in the pre-cycle, 79.2% in cycle I and 91.7% in cycle II. The indicator of using many flat geometric shapes increased from 54.2% in the pre-cycle, 87.5% in cycle I and 95.8% in cycle II. The average of all indicators increased from the pre-cycle 56.25% to cycle I at 70.83% and 81.25% in cycle II. In conclusion, learning using the PjBL model can enhance students’ creativity in creating two-dimensional works from flat geometric shapes.